Movement patterns of Brook Trout in a restored coastal stream system in southern Massachusetts. Issue 3 (6th March 2015) - Snook, Erin L.; Letcher, Benjamin H.; Dubreuil, Todd L.; Zydlewski, Joseph; O'Donnell, Matthew J.; Whiteley, Andrew R.; Hurley, Stephen T.; Danylchuk, Andy J.
Abstract: Coastal Brook Trout ( Salvelinus fontinalis ) populations are found from northern Canada to New England. The extent of anadromy generally decreases with latitude, but the ecology and movements of more southern populations are poorly understood. We conducted a 33‐month acoustic telemetry study of Brook Trout in Red Brook, MA, and adjacent Buttermilk Bay (marine system) using 16 fixed acoustic receivers and surgically implanting acoustic transmitters in 84 individuals. Tagged Brook Trout used the stream, estuary (50% of individuals) and bay (10% of individuals). Movements into full sea water were brief when occurring. GAMM models revealed that transitions between habitat areas occurred most often in spring and fall. Environmental data suggest that use of the saline environment is limited by summer temperatures in the bay. Movements may also be related to moon phase. Compared to more northern coastal populations of Brook Trout, the Red Brook population appears to be less anadromous overall, yet the estuarine segment of the system may have considerable ecological importance as a food resource.